Inducing hardening and healability in poly(ethylene-co-acrylic acid) via blending with complementary low molecular weight additives1. Issue 72 (12th December 2018) - Baker, Benjamin C.; German, I.; Stevens, Gary C.; Colquhoun, Howard M.; Hayes, Wayne
Abstract : Blending nitroarylurea gelators with poly(ethylene- co -acrylic acid) copolymers improves the mechanical and healing properties of the bulk polymer via 'network within a network' formation. Abstract : The design and synthesis of low molecular weight additives based on self-assembling nitroarylurea units, and their compatibility with poly(ethylene- co -acrylic acid) copolymers are reported. The self-assembly properties of the low molecular weight additives have been demonstrated in a series of gelation studies. Upon blending at low percentage weights (≤5%) with poly(ethylene- co -acrylic acid) the additives were capable of increasing the stress and strain to failure when compared to the parent copolymer. By varying the percentage weight of the additive as well as the type of additive the mechanical properties of poly(ethylene- co -acrylic acid) could be tailored. Finally, the healability characteristics of the blends were improved when compared to the original polymer via the introduction of a supramolecular 'network within a network'.